Fécamp et les rois anglo-normands - Judith Ann Green (Tabularia)
The experiences of the abbey of Fécamp can serve as an example of relations between the king-dukes and ecclesiastical magnates. The abbey had already acquired possessions in England before 1066 and assisted William’s expedition. The Conqueror held a brilliant court at Fécamp at Easter 1067. Afterwards the periods when England was held together with Normandy brought some advantages, but there were also problems, especially during the struggles between the sons of the Conqueror and between Stephen of Blois and the Angevins.